The influence of race duration on oxygen demand, uptake and deficit in competitive cross-country skiers - Gløersen, Ø.; Viken, Å.; Lund-Hansen, M.; Losnegard, T. (European Journal of Applied Physiology, 2024)
Purpose To measure oxygen demand, uptake, and deficits in competitive cross-country skiers during outdoor roller skiing at different competition durations, ranging from the endurance domain to the sprint domain.